Penggunaan Justice Collaborator Terhadap Efektivitas Penyelesaian Kasus Korupsi - Dima Sentosa; Asep Suherman (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
Corruption eradication in Indonesia is faced with complex challenges related to the important role of Justice Collaborators (JC) in exposing organized crime. This study was conducted to analyze how the use of JCs impacts the protection of suspects' rights and the effectiveness of corruption case disclosure. This study will examine the status of JCs, as regulated in SEMA No. 4 of 2011 and Law No. 31 of 2014, using a normative legal approach to demonstrate their role in the judicial process. Testimony from this study reveals that JCs are able to increase the evidentiary value in corruption cases; however, critical issues remain related to the implementation of legal protection and consistency in reducing sentences. Therefore, this study suggests improving protection instruments for JCs and increasing public awareness to help support JCs' role in combating corruption.